2020
DOI: 10.1186/s12889-020-09276-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors constraining utilization of contraceptive services among adolescents in Southeast Nigeria: an application of the socio-ecological model

Abstract: Background: High rate of teenage pregnancy in Nigeria is potentially an indication of poor access to and utilization of contraceptives among this age group. This paper presents findings from in-depth exploration of perceived barriers to utilization of contraceptive services by adolescents. Methods: A qualitative study was conducted in six communities in Ebonyi state, southeast Nigeria. Eighty-one in-depth interviews and six focus group discussions were conducted. Respondents comprised policy makers, community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 27 publications
6
55
0
2
Order By: Relevance
“…Adolescents mostly do not receive information from accurate sources such as experienced adults, parents and healthcare providers. Young people are most likely to receive and believe information they get through social media and friends as communication about SRH matters including contraceptives, barely occur in many African homes due to religious and cultural restrictions [ 6 , 29 ]. This finding corresponds with a Nigerian study by Envuladu et al which reported similar local/traditional methods used by women to prevent pregnancy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents mostly do not receive information from accurate sources such as experienced adults, parents and healthcare providers. Young people are most likely to receive and believe information they get through social media and friends as communication about SRH matters including contraceptives, barely occur in many African homes due to religious and cultural restrictions [ 6 , 29 ]. This finding corresponds with a Nigerian study by Envuladu et al which reported similar local/traditional methods used by women to prevent pregnancy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two FGDs were conducted in each community (giving a total of twelve) and participants ranged from 8 to 13 in number (see Table 1 below). A more comprehensive method of our study can be found in a published article [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…68 When selecting a contraceptive method, particularly IPP/ IPA, there is an onus on the provider to sensitively navigate the consultation, build trust, elicit the patient's needs and preferences, and ensure the decision to commence contraception is both well informed and not coerced. [70][71][72] Adolescents may require additional sexuality education and, due to heightened barriers to access and experiences of medical and social stigma, 28 require a supportive healthcare climate to facilitate education and decision-making. 73 Receiving inadequate information during contraceptive counseling, and the subsequent impact on contraceptive decisions, has implications for the reproductive autonomy of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Improving low rates of postpartum and post‐abortion care attendance, 22‐24 and subsequent use of contraception, has been the emphasis of a number of RRP‐focused interventions. Programs involving comprehensive follow‐up, home visits, education and family planning are the most effective for preventing repeat pregnancy and improving clinic attendance, 25,26 as these address social inequalities and improve poor health literacy and access to services 27‐29 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation